1968
DOI: 10.1136/jcp.21.4.501
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of the liver in hepatic porphyria

Abstract: SYNOPSIS In intermittent acute porphyria there are no specific alterations in the ultrastructure of the liver. In contrast, the constant characteristic of porphyria cutanea tarda is siderosis of the hepatocytes and Kupffer cells. Therefore, between the two types of hepatic porphyria there are no similar ultrastructural lesions. It is still doubtful whether the presence of hepatosiderosis in porphyria cutanea tarda is connected with the hepatopathy or is secondary to an alteration in the porphyrinic metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Survival rates were similar to transplantation for other indications, with 93% and 77% at 3 months and 5 years, respectively . Usually, explant is normal, except for siderosis in 7 of 10 explants resulting from chronic use of hemin therapy . None had preexistent or incidental HCC.…”
Section: Lt In Hepatic Porphryiamentioning
confidence: 63%
“…Survival rates were similar to transplantation for other indications, with 93% and 77% at 3 months and 5 years, respectively . Usually, explant is normal, except for siderosis in 7 of 10 explants resulting from chronic use of hemin therapy . None had preexistent or incidental HCC.…”
Section: Lt In Hepatic Porphryiamentioning
confidence: 63%
“…This was likely due to previous treatments with hemin because siderosis is not a reported feature of AIP in the absence of such therapy 11. Several other minor and nonspecific histological abnormalities were also observed that were not readily attributable to AIP.…”
Section: Resultsmentioning
confidence: 92%
“…Other liver function tests were also normal in these patients. It is known that hepatic histology by light microscopy (Goldberg & Rimington, 1962) and electron microscopy (Jean, Lambertenghi & Ranzi, 1968) is usually normal in AIP. It would thus appear that the effect of AIP on BSP excretion is not just a non-specific impairment of liver function.…”
Section: Discussionmentioning
confidence: 99%